On subharmonic extension and extension in the Hardy-Orlicz classes - Riihettiaus, J.; Tamrazov, P. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The paper contains a generalization of the results obtained earlier concerning the subharmonic extension of functions and the extension of functions in the Hardy-Orlicz classes. We give the unified proofs of these results.